The role of generative artificial intelligence in evaluating adherence to responsible press media reports on suicide: A multisite, three-language study - Zohar Elyospeh; Bénédicte Nobile; Inbar Levkovich; Raphael Chancel; Philippe Courtet; Yossi Levi-Belz (European Psychiatry)
Abstract